(untitled) (Journal of Dhaka Medical College, 2018)
Objective: To find out the effect of PROM on neonatal outcome so that we can pay more attention for the correct diagnosis and management of PROM in pregnancy which can reduce the perinatal mortality and morbidity caused by PROM. Methods: One hundred PROM cases were selected maintaining appropriate inclusion & exclusion criteria from the department of obstetrics & Gynaecology of BSMMU & DMCH and one hundred controlled cases were taken from the same during the period of January 2010 to December 2010. Data were analyzed with SPSS statistical program to determine the effect of PROM on neonatal health. Results: In this study, 44% babies of PROM patients had various type of morbidity compare to 24% of patients with intact membrane. In PROM patients, perinatal mortality was 7% in this study compare to 5% with intact membrane. Causes of perinatal death in PROM was severe asphyxia (4%), RDS (5%) & neonatal sepsis (6%) mainly. Conclusion: All fetal complications were significantly higher in PROM patients who received treatment after prolonged rupture of membrane. Appropriate antibiotic coverage in appropriate time will reduce fetal morbidity. J Dhaka Medical College, Vol. 26, No.2, October, 2017, Page 135-139